The contents of the serbian language syllabi and European integrations - Milovanović, Boško Lj.; Stakić, Mirjana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
After significant declarations: the Sorbonnne declaration (1988), Lisbon declaration (1997) and Bologna declaration (1999), there has emerged a need for fundamental changes in the educational systems of many European countries. These changes have also affected the Republic of Serbia. Globalization has introduced more radical changes in the educational process than those envisaged by the European declarations. The paper will theoretically consider the syllabus of the mother tongue in the Republic of Serbia and the consequences of the adaptation of our educational system to the European one. The paper analyses international and multicultural features of the Serbian language syllabus and their compliance with the contemporary processes of European integrations.